2016
DOI: 10.1016/s0022-3549(15)00175-6
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainable Release of Vancomycin and Its Degradation Products From Nanostructured Collagen/Hydroxyapatite Composite Layers

Abstract: Infections of the musculoskeletal system present a serious problem with regard to the field of orthopedic and trauma medicine. The aim of the experiment described in this study was to develop a resorbable nanostructured composite layer with the controlled elution of antibiotics. The layer is composed of collagen, hydroxyapatite nanoparticles, and vancomycin hydrochloride (10 wt%). The stability of the collagen was enhanced by means of cross-linking. Four cross-linking agents were studied, namely an ethanol sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…To date, the application of vancomycin-releasing collagen sponges as wound dressings has not been studied to any significant extent. Current approaches involve either the incorporation of other antibiotics into collagen sponges [1][2][3] or the use of vancomycin as one element of hydroxyapatite beads in the treatment of musculoskeletal injuries [4,5]. Moreover, various studies have described the administration of a vancomycin powder directly on surgical wounds so as to prevent wound infection following spinal, cardiac, or vascular surgery, with good effects [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the application of vancomycin-releasing collagen sponges as wound dressings has not been studied to any significant extent. Current approaches involve either the incorporation of other antibiotics into collagen sponges [1][2][3] or the use of vancomycin as one element of hydroxyapatite beads in the treatment of musculoskeletal injuries [4,5]. Moreover, various studies have described the administration of a vancomycin powder directly on surgical wounds so as to prevent wound infection following spinal, cardiac, or vascular surgery, with good effects [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Mammal collagens, such as calf or bovine, are the most used collagen types for biomaterial engineering [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in the vancomycin concentration could be related to its stability. Vancomycin can convert into its degradation products, which have a very similar chemical structure (Suchý et al, ). During our investigation, we did not observe the additional signals on the chromatograms (the DAD detector was used), thus we have concluded that the chemical structure of the vancomycin was not changed.…”
Section: Discussionmentioning
confidence: 99%
“…The increased effect was visible even after multiple bacterial inoculations. The ternary system containing hydroxyapatite, collagen, and vancomycin also seems to be an interesting solution [119][120][121]. For example, the purpose of the research of Egawa et al [122] was to determine the possibility of local antibiotic administration using the hydroxyapatite/collagen composite as a drug-delivery system.…”
Section: Conjugates Of Collagen/hap/vancomycin: Preparation and Applicationmentioning
confidence: 99%